Bulk Explosives Test Work at Duvha Opencast - T Davids; O J. Jordaan; M D. J Bonneau (International Society of Explosives Engineers, 1987)
As in most other parts of the world, the surface coal mining industry in South Africa is introducing emulsion explosives as the primary bulk blasting agent for use in wet borehole conditions where AN/FO cannot be used. Most of the emulsion products presently in use are gassed to provide sensitivity. The intimate mix between the fuel and oxidizer in the emulsion has been shown to produce a highly efficient explosive. However, a major difference between emulsion and the previous slurry products is its relatively low physical strength. This prompted Rand Mines' Duvha Opencast Mine, a major South African Escom power colliery, to conduct test work to illustrate the effect of emulsion physical consistency on blasthole loading. This paper presents the results of test work conducted at Duvha to investigate the problems associated with loading both AN/FO and emulsion in water filled holes, stemming emulsion holes, and in particular, to illustrate the difficulty in correctly introducing a stemming deck into the emulsion column. Time dependent behavior of the loaded emulsion holes is investigated. Velocity of detonation measurements for freshly manufactured emulsion, and for emulsion after loading through water with sleep times of up to 10 days, are presented.